Factors Affecting Tuberculosis in Asia: A Literature Review - Nopalia Resti Istikomah; Sulistiyani Sulistiyani; Nurjazuli Nurjazuli (JURNAL INFO KESEHATAN, 2025)
Tuberculosis (TB) remains a major public health concern in Asia, particularly in South and Southeast Asia. Comorbidities such as diabetes mellitus and HIV/AIDS substantially contribute to the regional TB burden, while multidrug-resistant tuberculosis (MDR-TB) continues to challenge TB control efforts. This study aimed to identify key factors associated with the high prevalence of TB in Asia and to highlight the need for integrated prevention and treatment strategies. A quasi-systematic literature review was conducted following PRISMA-based screening procedures. Peer-reviewed articles and official health reports published between 2015 and 2024 were systematically searched and assessed. After screening and eligibility evaluation, 15 studies were included in the final analysis. The results revealed consistent patterns indicating that diabetes mellitus significantly increases the risk of TB and worsens treatment outcomes, particularly in countries such as Indonesia, while HIV infection remains a major driver of active TB cases in Thailand and other high-burden settings. MDR-TB emerged as a critical regional threat, primarily associated with delayed diagnosis, limited laboratory capacity, shortages of trained healthcare personnel, and weak surveillance systems. Additionally, socioeconomic inequalities and inadequate healthcare infrastructure were recurrently identified as major barriers to effective TB control. In conclusion, reducing the TB burden in Asia requires a multifaceted and integrated approach addressing medical, social, economic, and health system factors. Strengthening diagnostic capacity, improving data reporting consistency, and enhancing regional collaboration are essential to achieving global TB elimination targets.